2006
DOI: 10.1152/ajpendo.00550.2005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progestagens differentially modulate vascular proinflammatory factors

Abstract: Duckles. Estrogen and progestagens differentially modulate vascular proinflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 43 publications
6
55
1
Order By: Relevance
“…Estrogenic abrogation of inflammation initiated by TNF-␣ is perhaps the most consistent of these effects and may be critical for linking infection to cardiovascular disease as TNF-␣ increases transiently even with low levels of lipopolysaccharide challenge (Jayachandran et al, 2007). Interestingly, in rats estrogen has been shown to suppress vascular inflammatory responses to IL-1␤ and lipopolysaccharide treatments, and this response has also been shown to vary through the estrous cycle (Galea et al, 2002;Ospina et al, 2004;Sunday et al, 2006). An intriguing result is that this anti-inflammatory effect of estrogen is lost in older female animals (Miller et al, 2004a;Sunday et al, 2007).…”
Section: A Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogenic abrogation of inflammation initiated by TNF-␣ is perhaps the most consistent of these effects and may be critical for linking infection to cardiovascular disease as TNF-␣ increases transiently even with low levels of lipopolysaccharide challenge (Jayachandran et al, 2007). Interestingly, in rats estrogen has been shown to suppress vascular inflammatory responses to IL-1␤ and lipopolysaccharide treatments, and this response has also been shown to vary through the estrous cycle (Galea et al, 2002;Ospina et al, 2004;Sunday et al, 2006). An intriguing result is that this anti-inflammatory effect of estrogen is lost in older female animals (Miller et al, 2004a;Sunday et al, 2007).…”
Section: A Inflammationmentioning
confidence: 99%
“…Thus, another possibility is that some of the various, little-studied estrogenic compounds in the CEE preparation were deleterious (Turgeon et al, 2004). Although animal studies have demonstrated untoward effects of medroxyprogesterone (Sunday et al, 2006), analysis of the CEEonly arm of the WHI appears to rule out this explanation (Barrett-Connor and Stuenkel, 1999;Turgeon et al, 2004;Hendrix et al, 2006). However, it is particularly notable that, in the Heart and Estrogen/Progestin Re-placement Study, only women with existing coronary disease were studied (Hulley et al, 1998), whereas in the WHI, the mean age of women at initial screening was 63 years, and more than 65% of the women were older than 60 years of age .…”
Section: Strokementioning
confidence: 99%
“…androgen; inflammation; vascular smooth muscle DESPITE THE GREATER INCIDENCE of stroke in men compared with age-matched premenopausal women (25a) and women's poorer outcomes following stroke (35), clinical studies regarding the effects of sex steroids on cerebral vascular pathophysiology remain a limited area of investigation. However, experimental research has shown that gonadal steroids modulate vascular inflammatory responses during pathological conditions (14,32,34,43). This is of great interest because the cerebral vasculature plays a central role in the pathogenesis of cardiovascular diseases, such as stroke (7), and in the initiation of inflammation after cerebral ischemia, which is a key determinant in stroke outcome (7,9).…”
mentioning
confidence: 99%
“…with LPS (0.1 or 1 mg/kg) or saline. At 4 h after injection, when fever reached a plateau and induction of vascular inflammatory enzymes was maximal (Cao et al, 1995;Sunday et al, 2006), the aorta was excised, and aortic rings Fig. 1.…”
Section: Methodsmentioning
confidence: 99%